Occupational health and food safety risks associated with traditional slaughter practices of goats in Gauteng, South Africa - Qekwana, D.N. (University of Pretoria, 2012)
Ritual slaughter of goats is a common practice in South Africa if the relative proportion of informal slaughter is taken into account. Religious, traditional or customary slaughter is legal in terms of meat safety legislation in South Africa. However, it is suggested that there is lack of understanding of basic food safety and occupational health concepts, and that this exposes the community to a wide spectrum of meat related hazards and food-borne diseases. Many hazards that are associated with traditional or customary slaughter of goats in South Africa have not been identified and characterized. The aim of the study was to identify, characterize and assess the occupational health and food safety risks of the biological, chemical or physical hazards associated with traditional slaughter of goats, by investigating the cultural practices and informal food chains associated with goats in South Africa. The study area was the Tshwane Metropole. A descriptive study, a form of qualitative research that describes the nature and the distribution of the outcomes, was conducted with 105 purposively selected adult respondents of both sexes at taxi ranks and places where commuters gather informally. A survey in the form of structured interviews using questionnaires was used. The data was analyzed using a thematic analysis method in conjunction with a statistical analysis. The abattoir or formal goat slaughter process, was considered as a baseline standard for comparison of meat hygiene and occupational health safety during traditional slaughter of goats. The traditional slaughter pathway, from farm to fork was derived based on structured interviews and compared to legislated norms for slaughter in red meat abattoirs. It was found that there were existing regulations for slaughter of goats at abattoirs, despite the fact that no goat abattoirs exist any longer in South Africa. Physical, chemical and biological hazards associated with ritual slaughter were identified and characterized. Qualitative data was analysed using Epi-info 7 (Centre of Disease Control, Atlanta, USA) and Microsoft Excel 2010 ® (Microsoft Corporation, USA). The magnitude and likelihood of identified biological hazards was estimated using qualitative risk assessment, modified after the method suggested for BSE in Cattle by FAO (2009). Methods of ritual slaughter differed between groups, but there was little pre-slaughter examination for disease and stunning was not used. Exsanguination could be improved by hanging the carcass and a more structured approach to decreasing contamination of the carcass by ingesta, soil, leaves and dirt could be prioritized. It was recommended that veterinary services pay more attention to the health of goats in South Africa, as these are not regularly examined at post mortem, as are other livestock where routine surveillance for disease is carried out at registered abattoirs. Information on how to determine if a goat that is bought for slaughter is healthy, based on veterinary extension and communication, should be communicated to rural communities. A simple pamphlet or poster could be developed and distributed to commuters at taxi stops, or distributed by Animal Health Technicians in rural areas. Meat hygiene principles, linked to practical hygiene principles such as the WHO “five keys” should also be communicated within rural communities and applied to informal slaughter. The principles of good hygiene and meat safety, are, however, the same. Veterinary services could be involved in actual training of those who regularly slaughter goats to make sure that they cut the throat cleanly and the goat is exsanguinated properly. Welfare of goats during slaughter could be improved by paying more attention to humane transport and restraint as well as the use of sharp knives. Research needs to be done on a practical way of stunning under rural conditions. This however should not infringe upon people’s cultural norms and religious beliefs.